Katyn massacre : basic facts - Komaniecka, Monika (The person and the challenges, 2013)
Katyn is a symbol of the criminal policy of the Soviet system against the Polish nation. The present study aims to demonstrate the basic facts of Katyn massacre - the execution of almost 22,000 people: Polish prisoners of war in Katyn, Kharkov, Kalinin (Tver) and also other Polish prisoners (soldiers and civilians), which took place in the spring of 1940 in different places of the Soviet Ukraine and Belarus republics based on the decision of the Soviet authorities, that is the Political Bureau of All-Union Communist Party (Bolsheviks) of March 5, 1940. This article refers not only to the massacre itself, but also its origin, historical processes and the lies accompanying Katyn massacre